Organizational learning contracts : new and traditional colleges - Goodman, Paul S. (New York ; Oxford : Oxford University Press, 2011)
The state of higher education today is one of change and stasis. Economic vulnerability, globalization, technological innovation and an increasingly competitive market underlie the need for change in higher education.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Keywords: Learning contracts; Education, Higher